2020
DOI: 10.1136/bmjopen-2019-035376
|View full text |Cite
|
Sign up to set email alerts
|

Place, poverty and prescriptions: a cross-sectional study using Area Deprivation Index to assess opioid use and drug-poisoning mortality in the USA from 2012 to 2017

Abstract: ObjectiveTo identify the relationships between county-level area deprivation and patterns of both opioid prescriptions and drug-poisoning mortality.Design, setting and participantsFor this retrospective cross-sectional study, we used the IQVIA Xponent data to capture opioid prescriptions and Centres for Disease Control and Prevention National Vital Statistics System to assess drug-poisoning mortality. The Area Deprivation Index (ADI) is a composite measure of social determinants of health comprised of 17 US ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
0
35
1
Order By: Relevance
“…Red diamonds depict major cites (Albuquerque in Bernalillo County, Las Cruces in Dona Ana County, Rio Rancho in Sandoval County, and Santa Fe in Santa Fe County). ADI scores were developed by Mayo Clinic researchers ( 10 ), and are derived from 17 indicators that served as surrogates for income, employment, housing, and education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Red diamonds depict major cites (Albuquerque in Bernalillo County, Las Cruces in Dona Ana County, Rio Rancho in Sandoval County, and Santa Fe in Santa Fe County). ADI scores were developed by Mayo Clinic researchers ( 10 ), and are derived from 17 indicators that served as surrogates for income, employment, housing, and education.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we considered 443,814 non-Hispanic AI/AN and non-Hispanic White women aged 15 years or older at risk for breast cancer. These data were extended to include county-level Area Deprivation Index (ADI) scores developed by Mayo Clinic researchers ( 10 ), which were measured from 17 indicators that served as a surrogate for income, employment, housing, and education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conflicting and limited evidence emphasizes the necessity for further studies evaluating patient knowledge of opioids in orthopaedic surgery. Our findings may reflect that patients of lower socioeconomic measures and from more disadvantaged geographic regions are more frequently exposed to opioid prescription, chronic consumption, and related overdose in their communities [ 38 41 ]. This exposure, in turn, may translate to greater knowledge regarding opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The ADI score is a composite indicator of area-based socioeconomic disadvantages in the 4 domains outside of the strictly defined health care setting: income, housing, employment, and education. Previous studies have revealed disparities in cancer screening, 20 opioid use, 21 and drug-related mortality 21 as a function of the ADI score. However, evidence is scarce on the association between area-level deprivation (as captured by a multifaceted indicator of social determinants of health, such as the ADI) and diabetes care quality.…”
Section: Introductionmentioning
confidence: 99%